Pengaruh Program Sekolah Ramah Anak Terhadap Moralitas Peserta Didik Kelas XI di MAN 9 Jombang - Rosyidah Uzlifatul Jannah; M Wafiyul Ahdi; Emi Lilawati (Universitas KH. A. Wahab Hasbullah, 2022)
This research aims to find out the influence of child-friendly school programs on the morality of class XI learners at MAN 9 Jombang. This type of research is quantitative research with a type of correlational design. The data taken from the sample of 60 students was collected using observations, questionnaires by spreading a list of questions through google forms links and answered online by respondents, and documentation. It is then analyzed using product moment analysis techniques. The results of this study used product moment analysis of 0.312 > 0.254 so that H0 was rejected and Ha accepted. Thus it can be concluded that there is a significant influence between the influence of the Child Friendly School Program on the morality of class XI learners in MAN 9 Jombang.